Fundamental orthopedic management for the physical therapist assistant - Shankman, Gary A.; Manske, Robert C. (St. Louis, Mo. : Mosby/Elsevier, 2011)
medications, and associated movements.
Includes bibliographical references and index.
Keywords: Orthopedic Procedures; Allied Health Personnel; Physical Therapy Modalities